Identification of IQGAP1 as a SLC26A4 (Pendrin)-Binding Protein in the Kidney - Xu, Jie; Barone, Sharon; Varasteh Kia, Mujan; Holliday, L. Shannon; Zahedi, Kamyar; Soleimani, Manoocher (Frontiers in Molecular Biosciences, 2022)
Background: Several members of the SLC26A family of transporters, including SLC26A3 (DRA), SLC26A5 (prestin), SLC26A6 (PAT-1; CFEX) and SLC26A9, form multi-protein complexes with a number of molecules (e.g., cytoskeletal proteins, anchoring or adaptor proteins, cystic fibrosis transmembrane conductance regulator, and protein kinases). These interactions provide regulatory signals for these molecules. However, the identity of proteins that interact with the Cl−/HCO3− exchanger, SLC26A4 (pendrin), have yet to be determined. The purpose of this study is to identify the protein(s) that interact with pendrin. Methods: A yeast two hybrid (Y2H) system was employed to screen a mouse kidney cDNA library using the C-terminal fragment of SLC26A4 as bait. Immunofluorescence microscopic examination of kidney sections, as well as co-immunoprecipitation assays, were performed using affinity purified antibodies and kidney protein extracts to confirm the co-localization and interaction of pendrin and the identified binding partners. Co-expression studies were carried out in cultured cells to examine the effect of binding partners on pendrin trafficking and activity. Results: The Y2H studies identified IQ motif-containing GTPase-activating protein 1 (IQGAP1) as a protein that binds to SLC26A4’s C-terminus. Co-immunoprecipitation experiments using affinity purified anti-IQGAP1 antibodies followed by western blot analysis of kidney protein eluates using pendrin-specific antibodies confirmed the interaction of pendrin and IQGAP1. Immunofluorescence microscopy studies demonstrated that IQGAP1 co-localizes with pendrin on the apical membrane of B-intercalated cells, whereas it shows basolateral expression in A-intercalated cells in the cortical collecting duct (CCD). Functional and confocal studies in HEK-293 cells, as well as confocal studies in MDCK cells, demonstrated that the co-transfection of pendrin and IQGAP1 shows strong co-localization of the two molecules on the plasma membrane along with enhanced Cl−/HCO3− exchanger activity. Conclusion: IQGAP1 was identified as a protein that binds to the C-terminus of pendrin in B-intercalated cells. IQGAP1 co-localized with pendrin on the apical membrane of B-intercalated cells. Co-expression of IQGAP1 with pendrin resulted in strong co-localization of the two molecules and increased the activity of pendrin in the plasma membrane in cultured cells. We propose that pendrin’s interaction with IQGAP1 may play a critical role in the regulation of CCD function and physiology, and that disruption of this interaction could contribute to altered pendrin trafficking and/or activity in pathophysiologic states.